Adsorption of Phosphate by Surface Precipitation on Lanthanum Carbonate Through In Situ Anion Substitution Reactions - Zhang, Shaoyang; Xie, Fazhi; Tang, Zhi; Zhao, Tianhui; Fang, Mengyuan; Giesy, John P. (Frontiers in Environmental Science, 2022)
Efficient removal of phosphate (PO43−) is the main solution to control eutrophication. In this study, lanthanum carbonate (La2(CO3)3) was the adsorbent of choice for the removal of PO43−. Both adsorption isotherm and thermodynamic were investigated. La2(CO3)3 was an effective adsorbent for the removal of phosphate (PO43− or H2PO4−) under weak acidic conditions (pH = 2.0–6.0); the maximum adsorption amount was 106.6 mg g−1 at pH 2.9. The pHzpc of La2(CO3)3 changed from 2.1 to 6.5 prior to and after adsorption of PO43−. The adsorption of PO43− on the surfaces of La2(CO3)3 was an endothermic process. With the increase of anions, the adsorption efficiency of PO43- decreased. The presence of natural organic matter also inhibited the adsorption of PO43−, but the interference was weaker than that of anions. The mechanisms of adsorption were investigated by various techniques including Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), powder X-ray diffraction (XRD), and X-ray photoelectron spectroscopy (XPS). Based on the results obtained using XPS, during the adsorption process of PO43− on La2(CO3)3, La3+ was released and could precipitate with PO43− or H2PO4− under weak acidic conditions (pH = 2.0–4.0). Adsorption was dominated by in situ substitution reactions between CO32− and H2PO4− or HPO42−. This study provides a useful reference and potential material for the removal of PO43− in aquatic environments.